Development of Android-Based Indonesian Cultural Exploration Educational Game for Madrasah Ibtidaiyah Students - Rofiatun Nisa'; Nukh Khozain (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2023)
This research aims to develop an Android-based educational game to introduce Indonesian culture to Madrasah Ibtidaiyah students.  Following the Research and Development methodology with ADDIE model, the study comprises three key stages:  1) analysis of students' and teachers' needs, 2) development of the educational game, and 3) testing the product's effectiveness. The study involved test subjects from twenty schools in Lamongan Regency.  Data were collected using questionnaires and interviews, and data analysis encompassed both qualitative and quantitative methods.   The material expert validation, media validation, and validation by learning experts collectively resulted in a 'very good' categorization. The educational game's effectiveness was substantiated by a t-test (tvalue > ttable) and practicality tests, revealing a high interest level of 94.86%. In conclusion, this research significantly contributes to the development of an Android-based educational game for exploring Indonesian culture.